Characterization and control of antibiotic-resistant camalti saltern's isolates with bacteriocins - (:unkn) unknown (My University, 2022)
Camalti Saltern is the largest solar saltern in Izmir, Turkey. The salt obtained from Camalti Saltern is used in food and leather industries to prevent bacterial growth. In this saltern, seawater is pumped into shallow ponds. Then, the sun and wind cause evaporation and crystallization, finally sea salt is produced. Due to the fact that Camalti Saltern contains various halophilic bacteria, the goals of the present study were to isolate and identify haloversatile bacteria from Camalti Saltern\"s brine samples, to examine their antibiotic resistance profiles, to determine antimicrobial activities under optimum environmental conditions, to determine bacteriocin concentration by Bradford Method, to detect Minimum Inhibitory Concentrations (MIC) and Minimum Bactericidal Concentrations (MBC) of bacteriocins against multidrug-resistant isolates, and to observe the cell structure of bacteriocin-treated bacteria under SEM. Sixteen bacterial isolates were recovered from Camalti Saltern\"s brine samples and were identified as 14 different species (Bacillus haynesii, Bacillus simplex, Bacillus subtilis subsp. stercoris, Bacillus pumilus, Staphylococcus petrasii subsp. jettensis, Staphylococcus saprophyticus subsp. saprophyticus, Kocuria sediminis, Rhodococcus enclensis, Marinobacter hydrocarbonoclasticus, Vibrio olivae, Marinomonas communis, Pseudomonas psychrotolerans, Salinivibrio costicola subsp. vallismortis, Vibrio neocaledonicus). Percentages of antibiotic resistance of isolates were 63% to aztreonam, 50% to amoxicillin/ clavulanic acid, 44% to ampicillin, 44% to cefadroxil, 31% to imipenem, 19% to ampicillin/sulbactam, 6% to chloramphenicol, 6% to tetracycline, 6% to mupirocin, 6% to meropenem. The bacteriocin concentrations of Rhodococcus enclensis and Salinivibrio costicola subsp. vallismortis were measured as 1.02 mg/mL and 1.25 mg/mL, respectively. Bacteriocins of Rhodococcus enclensis and Salinivibrio costicola subsp. vallismortis, which were not resistant to any antibiotics tested, exhibited the inhibitory effect against Kocuria sediminis resistant to ten antibiotics and Bacillus pumilus resistant to four antibiotics. Bacteriocin of Salinivibrio costicola subsp. vallismortis also demonstrated the inhibitory effect against Pseudomonas psychrotolerans resistant to five antibiotics. Scanning electron micrographs showed that cell morphologies of bacteriocintreated isolates (Kocuria sediminis, Bacillus pumilus, Pseudomonas psychrotolerans) were damaged. In conclusion, bacteriocins produced from the haloversatile Camalti saltern isolates may be used in the leather industry to prevent the growth of antibiotic-resistant haloversatile bacteria.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Textile Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; General Materials Science; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences